PENGARUH MEDIA MONOPOLI TERHADAP MINAT BELAJAR IPS SISWA KELAS III SDN 79 PALEMBANG - Della Berliani; Zahrudin Hodsay, Anggria Septiani Mulbasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of monopoly media on students' interest in learning social studies in class III SD Negri 79 Palembang. This study includes quantitative and experimental research using two classes, namely the control class and the experimental class. The population used was 181 people, with sampling obtained class III A as many as 30 people as the experimental class and III C as many as 30 people as the control class. Data analysis used the Normality test, 0,078 > 0,05 Homogeneity test, 0,011 < 0,05 and Hypothesis test, 0,000 < 0,05. The data collection technique was in the form of a questionnaire. The conclusion of this study shows that monopoly media has an effect on the learning interest of class III students of SD Negri 79 Palembang, namely in the experimental class 65, the results are in the control class 40. this proves that monopoly media has an effect on students' learning interest.